Effectiveness of Suctioning and Factors Affecting ; A Systematic Review - Lesmana, Hendy (Caring: Indonesian Journal of Nursing Science, 2019)
Suction is a routine action performed by nurses who work in a critical care setting. every patient who has decreased consciousness and installed a definitive air way will always get a suction action that is useful for keeping the airway free of mucus so that airway patency is maintained. The purpose of this literature review is to identify and summarize the results of research and books on factors that influence the effectiveness of suction. This study is a literature review that tries to find and explore more information about the effectiveness of suction. The method used in this literature review begins with topic selection, keyword determination to search journals through the Google Scholar, Ebscho, and Pro Quest databases. The articles used were 16 articles and 7 books. Literature search results obtained namely; factors affecting the effectiveness of suction are; assessment before performing suction, pre hyperoxygenation measures, effective suction pressure regulation, suction canule size must pay attention to the ETT diameter / size, suction action time 10-15 seconds for adults and 5 seconds for infants and children, suction techniques and must consider volume and mucus viscosity. The conclusion in conducting effective suction, nurses must pay attention to these 7 factors rather in the implementation of suction actions to be more effective and avoid unwanted side effects.